As orações subordinadas substantivas em função de sujeito: questões de ensino - Gasparine Bastos, Sandra Denine [UNESP]; Hattnher, Marize Mattos Dall'Aglio [UNESP]; Gonçalves, Sebastião Carlos Leite [UNESP] (My University, 2013)
This paper attempts to answer how the descriptive analysis of the substantive subordination clauses made within the realm of academic research can contribute to the effective teaching of those structures in the Elementary School. After showing how the subordination has been treated in grammar school and textbooks and pointing at some recurring problems in the presentation of the subject, we present the treatment of subordinate clauses with the function of subject in two descriptive grammars of Portuguese, in order to ascertain to what extent the relevant aspects of the description of those clauses are related to the traditional way of teaching. From those descriptive works, we selected some functional features considered to be essential for the treatment of the subject in the Elementary School.

Este trabalho procura responder como a descrição das orações subordinadas substantivas, feita no âmbito acadêmico, pode contribuir para o ensino dessas estruturas no âmbito escolar. Depois de mostrar como a subordinação vem sendo tratada em gramáticas escolares e em livros didáticos usados no segundo ciclo do Ensino Fundamental e apontar alguns problemas recorrentes no tratamento do tema, apresentamos o tratamento dado às orações subordinadas substantivas em função de sujeito em duas gramáticas descritivas do português, com o propósito de verificar em que medida os aspectos relevantes da descrição dessas orações estão relacionados ao modo tradicional de ensino. A partir desses trabalhos descritivos, selecionamos algumas características funcionais que consideramos essenciais para o tratamento do tema no ensino escolar.
Subordinate clauses acting as subject: ussues related to teaching
Keywords: subordinação; oração subjetiva; ensino; Subordination; teaching; textbooks; Portuguese